Development of Immersive VR Device for Gait Training Rehabilitation with Biofeedback System-Preliminary Study - Jeong-Woo Seo (MDPI AG, 2021)
Gait-training rehabilitation machines (MGTR) are contraptions used for the motor rehabilitation of patients with movement disorders resulting from stroke and Parkinson’s disease. This study was aimed at implementing a walking pattern similar to the normal gait. Background: Immersion and motivation are important factors in repetitive rehabilitation exercises. This was addressed by synchronizing walking speed and virtual reality (VR) visons to provide a sense of immersion in a convergence environment of MGTR and VR. Methods: The difference in joint angle and gait event was confirmed when the step length was adjusted in this system to control the joint movement. Results: It was confirmed that the joint range of motion also increased significantly as the step length increased. Conclusions: The possibility of developing a more immersive MGTR system that feedback the actual gait state in the VR system was confirmed by applying that the joint movement varies according to the step length. It will be possible to provide an immersive feeling more similar to the actual walking by modifying the gait trajectory of the MGTR.